Optimization of the thermal performance of building double-skin envelope - Chua, Wei Jin (2014)
Singapore is geographically situated close to the earth's equator. Thus, Singapore does not experience any seasonal change instead, Singapore experience a hot and humid climate throughout the year. Due to the hot and humid climate that Singapore experience throughout the year, residence of Singapore rely a lot on the use of the air-conditioner to achieve thermal comfort in their everyday life. But it was found that the excessive use of air-conditioner, not only in Singapore, has given rise in the mean global temperature or in other words, global warming. Therefore, to slow down the rise in the mean global temperature, a double-skin roof technology was used to reduce the heat produced by the sun from getting into the building. When less heat gets into the building, thermal comfort can be achieved much easily and also reducing the usage of air-conditioner.